Sub-acute post traumatic ascending myelopathy with superimposed infection in a diabetic: a case report - Shenoy, Shreya; Prasath, C. S. Vishnu; R., Manish; Bala, Sargunan (International Journal of Research in Orthopaedics, 2024)
Subacute posttraumatic ascending myelopathy (SPAM) is a rare entity associated with trauma to the spinal cord, usually at the level of the thoracic spine. Patient presents with neurological deterioration 4 or more levels above the site of primary injury. It usually follows an episode of fever unrelated to infection. A 43-year-old diabetic male patient with history of blunt trauma to thoracic spine with T5 flexion distraction injury with ASIA A neurology, underwent T3-T6 posterior instrumented stabilisation. Four weeks following this, he presented with signs of encephalopathy with CSF culture showing Acinetobacter baumanii. Though the patient had improvement with culture- sensitivity appropriate antibiotics, he developed ascending neurological deficits on day 3 of admission. On repeat MRI, he showed cord oedema up to C3. He was started on steroids and showed remarkable clinical improvement. SPAM must be kept as a differential in the diagnosis of a postoperative event with similar clinical picture.